Operation and control of triphase power converter integrated with lithium-ion battery - Tan, Yi Da (Nanyang Technological University, 2020)
This report serves to provide a formal documentation on how to operate and control the Triphase power converter integrated with the Saft lithium-ion battery, which are in Clean Energy Research Lab (CERL) in Nanyang Technological University (NTU), using the MATLAB/Simulink and PCAN-View software. In addition, a more user-friendly graphical user interface (GUI) to control the voltage level of the Triphase power converter and current level of the lithium-ion battery is created using LabVIEW, which serves as an extension of the MATLAB/Simulink software. An external pre-charge current limit circuit is also built in order to reduce the high transient power demand from the microgrid in CERL. With the implementation of this pre-charge current limit circuit, the Triphase power converter and the Saft lithium-ion battery can be properly integrated with the microgrid in CERL, paving the way for researchers to conduct future experiments using the Triphase power converter with the microgrid.